A 3d game in python - Xu, Minghui (2014)
3D game has widely been accepted and loved by many game players. More and more different kinds of 3D games were developed to feed people’s needs. The most common programming language for development of 3D game is C++ nowadays. Python is a high-level scripting language. It is simple and clear. The concise syntax could speed up the development cycle. This project was to develop a 3D game using only Python. The game is about how a cat lives in the street. In order to live, the player need to find food and water. At the same time, the player needs to keep away from the dogs. After this project, it would show how Python could perform in programming a 3D game.